Study of the expression of different genes of long-chain polyunsaturated fatty acids (LC-PUFA) metabolism during the early paralarval development of the common octopus (Octopus vulgaris) - Moura, Joana Maria Teixeira de (2016)
Dissertação de mestrado, Aquacultura e Pescas, Faculdade de Ciências e Tecnologias, Universidade do Algarve, 2015